2010
DOI: 10.1152/ajpgi.00379.2009
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic AMP-mediated endocytosis of intestinal epithelial NHE3 requires binding to synaptotagmin 1

Abstract: The apical membrane Na(+)-H(+) exchanger (NHE)3 is regulated by cAMP-dependent phosphorylation, which inhibits its activity through membrane endocytosis. The clathrin complex adaptor protein synaptotagmin 1 (Syt 1) appears to be essential to this process, but little is known about its expression in intestinal epithelial cells or interaction with NHE3. The intestinal epithelial expression and apical location of Syt 1 were determined by Syt 1 mRNA profiling and immunolocalization. Tandem mass spectrometry was us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 48 publications
2
14
0
Order By: Relevance
“…Interestingly, and similar to our results, Chang and colleagues (36,37) recently demonstrated that synaptotagmin 1 is present in intestinal epithelial cells by RT-PCR, immunoblotting and direct sequencing, and further showed synaptotagmin 1 localizes to the apical membrane by immunofluorescence. We also found that synaptotagmin 1 localized to the apical aspects of acini but surprisingly showed incomplete overlap with VAMP-2 on the plasma membrane.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Interestingly, and similar to our results, Chang and colleagues (36,37) recently demonstrated that synaptotagmin 1 is present in intestinal epithelial cells by RT-PCR, immunoblotting and direct sequencing, and further showed synaptotagmin 1 localizes to the apical membrane by immunofluorescence. We also found that synaptotagmin 1 localized to the apical aspects of acini but surprisingly showed incomplete overlap with VAMP-2 on the plasma membrane.…”
Section: Discussionsupporting
confidence: 91%
“…Synaptotagmin 1 was highly localized to the apical membrane of enterocytes in the small intestine and was likewise present in a colon carcinoma cell line (Caco-2BBe) (36,37). Expression of synaptotagmin 1 was confirmed by RT-PCR, immunoblotting, small interfering RNA (siRNA) studies and by direct sequencing of the immunoprecipitated protein.…”
mentioning
confidence: 92%
“…Calcium Inhibition of NHE3 Activity in Polarized OK Cells-NHE3 is acutely inhibited by elevation in the concentration of intracellular Ca 2ϩ by the cholinergic agonist carbachol (24 -26) as well as by serotonin (27), adenosine 1 receptor agonists (9), and thapsigargin and Ca 2ϩ ionophores (18,28,29). Decreased NHE3 activity also occurs in PS120 fibroblasts with Ca 2ϩ ionophores (10,11).…”
Section: Resultsmentioning
confidence: 99%
“…Clathrin-and caveolin-dependent pathways are well-defined cellular endocytic routes previously shown to be involved in the basal and regulated internalization of ion transporters (21,26,27,33,37). The endocytosis inhibitor dynasore inhibits dynamin, a 100-kDa GTPase required to pinch-off coated vesicles from the plasma membrane, and, thereby, prevents both clathrin-and caveolin-dependent endocytosis (23).…”
Section: Role Of Dynamin-dependent Endocytic Pathways In Regulating Amentioning
confidence: 99%